A paisagem de Ouro Preto - Maria Manoela Gimmler Netto (2014)
This dissertation, "The landscape of Ouro Preto" understands the landscape as a product of the interaction between man and the environment. The built environment reflects a cultural process of a community in a given territory over time, forming the identity of the landscape. The characterization is what allows the knowledge of the identity and consists in the objective of this work qualify the intrinsic characteristics of the landscape of Ouro Preto. The landscape analysis, in this research covers three categories of qualities of the landscape: environmental, functional and aesthetic. Each category contains its potential and its frailty. Thus, environmental quality considers the relief as the principal determinant of the morphology of the landscape of Ouro Preto. Functional quality is investigated through urban morphology for understanding occupation and urbanization process. And the aesthetic quality aims to identify landscape features that are culturally recognized, through the interpretation of the representation of two artists who understood and recorded in paintings the landscape of Ouro Preto at different times in its history. The character of the landscape of Ouro Preto is defined by elements that define their identity. Refer mainly to the geomorphology and the association between topography and different forms of occupation. Moreover, presents a significant process of historical development, which reveals its historicity, understood as apparent permanence of the passage of time. This translates as infinite potential for research, values and perceptions. However, like every city, presents trends to changes and expansions that need to be managed to guarantee continuity of the identity of the landscape. This study sought to contribute to the landscape characterization of Ouro Preto understood as a cultural asset. It is concluded that the weaknesses often arise from ignorance of the environment by man or inadequacy of their intervention. Therefore inadequate forms of urban occupation accelerate natural processes inherent to the environment. With this dissertation, is expected to point out possible ways for contemporary landscape management of Ouro Preto that must take into account the characteristics that make it unique. In conclusion that knowledge of the character of the landscape is the principle to its sustainable development, provide a way of guidance to public policy.